A Rare Colocalization of Lichen Planus and Vitiligo - David Veitch; Georgios Kravvas; Sian Hughes; Christopher Bunker (Hindawi Limited, 2015)
We report an unusual manifestation of vitiligo colocalizing with lichen planus (LP). A 76-year-old Greek male presented with a history of a red, scaly, itchy, asymmetrical patch located at the umbilicus within a well-demarcated depigmented macule of vitiligo. Histology showed features of a lichenoid interface dermatitis, favouring a diagnosis of LP. Colocalization of LP and vitiligo has rarely been reported in the literature. After reviewing the literature, we believe that at present there is insufficient evidence to resolve the uncertainties in the aetiology of this colocalization. It seems to us that the association between LP and vitiligo is more than coincidental, but none of the theories discussed in this paper can sufficiently account for it. Rather, the association is likely to be multifactorial in its pathogenesis.